Construction of a Keggin heteropolyacid/Ni-MOF catalyst for esterification of fatty acids. Issue 53 (13th October 2021) - Zhang, Qiuyun; Luo, Qizhi; Wu, Yaping; Yu, Rongfei; Cheng, Jingsong; Zhang, Yutao
Abstract : The developed heteropolyacids immobilized on Ni-MOF catalysts have strong acidity and perform well in esterification. Abstract : This work reports the one-pot solvothermal synthesis of a Keggin heteropolyacid (phosphomolybdic acid, tungstophosphoric acid, or silicotungstic acid) immobilized on Ni-MOF composite catalysts for esterification of fatty acids, and the composites were further analyzed by XRD, FTIR, NH3 -TPD, SEM, TEM, N2 adsorption/desorption, and XPS. Among the contrastive syntheses ( i.e., HPW/Ni-MOF, HSiW/Ni-MOF, and HPMo/Ni-MOF), HPMo/Ni-MOF exhibits the most active catalyst toward fatty acids esterification, and the characterization results also revealed that HPMo/Ni-MOF has a strong acidity, large specific surface area, and appropriate average pore size. More significantly, this catalyst exhibits a good catalytic performance (86.1% conversion) during esterification under the optimized reaction conditions, and the HPMo/Ni-MOF catalyst can remain stable after the tenth cycle with a conversion of 73.5%. Intriguingly, the esterification reaction kinetics was studied, and the activation energy was found to be 64.6 kJ mol −1 . The results indicated that the esterification of fatty acids using the HPMo/Ni-MOF catalyst is a chemically controlled reaction.